2021
DOI: 10.1111/cge.13920
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic deletion in a minimal CAPN15 intron in siblings with a recognizable syndrome of congenital malformations and developmental delay

Abstract: Calpainopathies constitute a heterogeneous group of disorders resulting from deficiencies in calpains, calcium‐specific proteases that modulate substrates by limited proteolysis. Clinical manifestations depend on tissue‐specific expression of the defective calpain and substrate specificity. CAPN15, encoding the Drosophila small optic lobes (sol) homolog, was recently found to cause various eye defects in individuals carrying bi‐allelic missense variants. Here we report on two siblings with manifestations remin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…MRI results showed that the Capn15 KO brain was 14% smaller in volume compared to the WT animals and the weight of the brain was similarly reduced. One human individual with a biallelic variant CAPN15 had clinical microencephaly (Zha, et al, 2020) as did a patient with a likely loss of function of CAPN15 (Mor-Shaked et al, 2021), consistent with the mouse recapitulating a loss of brain volume also seen in humans. The total change in brain volume was similar to the 11% weight loss, although there is no correlation between body and brain weight in mice (Spring et al, 2007).…”
Section: Discussionsupporting
confidence: 52%
“…MRI results showed that the Capn15 KO brain was 14% smaller in volume compared to the WT animals and the weight of the brain was similarly reduced. One human individual with a biallelic variant CAPN15 had clinical microencephaly (Zha, et al, 2020) as did a patient with a likely loss of function of CAPN15 (Mor-Shaked et al, 2021), consistent with the mouse recapitulating a loss of brain volume also seen in humans. The total change in brain volume was similar to the 11% weight loss, although there is no correlation between body and brain weight in mice (Spring et al, 2007).…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, Capn15 knockout mice show that Capn15 expression throughout the brain and central nervous system is high early in development and decreases postnatally. The mice with complete loss of Capn15 have smaller brains with larger decreases in the thalamus and in subregions of the hippocampus (Mor‐Shaked et al, 2021; Zha et al, 2020; Zha et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…OGIN syndrome encompasses different ocular features (colobomas, microphthalmia, ptosis, myopia, cataract, iridocorneal adhesions, optic gliosis), as well as imperforate anus, rectovesical fistula, genitourinary anomalies (horseshoe kidney, ureteropelvic junction dysfunction, vesicoureteral reflux, vaginal fistula), cardiac anomalies (atrial or ventricular septal defect, patent ductus arteriosus, bicuspid aortic valve, pulmonary stenosis, right aortic arch), skeletal anomalies (hemivertebrae, sacral dysplasia), hearing loss, laryngeal cleft (less frequently observed), severe developmental delay (with absent speech in some patients), growth delay, cognitive delay, axial hypotonia, microcephaly, demyelination, cortical atrophy, mild ventricular dilation, seizures, and autistic features in some patients; however other patients have normal motor and cognitive development (Mor‐Shaked et al, 2021; Zha et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Following informed consent, exome sequencing analysis was performed on DNA extracted from whole blood of the proband (individual IV-1) and the parents, as previously described [37][38][39]. Exonic sequences were enriched from the genomic DNA samples using SureSelect Human All Exon v.5 50 Mb Kit (Agilent Technologies, Santa Clara, CA, USA).…”
Section: Exome Analysismentioning
confidence: 99%